2011
DOI: 10.1590/s0100-736x2011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Sparrows (Passer domesticus L.) as intermediary hosts of Toxoplasma gondii in poultry farms from the "agreste" region of Pernambuco, Brazil

Abstract: This paper aimed to identify Toxoplasma gondii infection in house sparrows (Passer domesticus, Linneaus 1758) coming from poultry farms in the "agreste" region of the Brazilian state of Pernambuco. 151 sparrows (Passer domesticus) captured in eight broiler, egg layer and commercial laying poultry farms, were used. Indirect hemagglutination test was used to research anti-T. gondii antibodies. Animals that presented titration of 1:16 were destined to DNA research through Polymerase Chain Reaction (PCR) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
(4 reference statements)
0
5
0
3
Order By: Relevance
“…Molecular frequency of T. gondii in sparrows was also reported in Brazil (Gondim et al 2010;Vilela et al 2011) and China (Cong et al 2013;Huang et al 2012). In this regard, Gondim et al (2010) detected anti-Toxoplasma antibodies in 1.02 % (3/293) and T. gondii DNA from 17.5 % (7/40) of sparrows in the northeast of Brazil (Gondim et al 2010).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Molecular frequency of T. gondii in sparrows was also reported in Brazil (Gondim et al 2010;Vilela et al 2011) and China (Cong et al 2013;Huang et al 2012). In this regard, Gondim et al (2010) detected anti-Toxoplasma antibodies in 1.02 % (3/293) and T. gondii DNA from 17.5 % (7/40) of sparrows in the northeast of Brazil (Gondim et al 2010).…”
Section: Discussionmentioning
confidence: 52%
“…In this regard, Gondim et al (2010) detected anti-Toxoplasma antibodies in 1.02 % (3/293) and T. gondii DNA from 17.5 % (7/40) of sparrows in the northeast of Brazil (Gondim et al 2010). Vilela et al (2011) reported 60.3 % (90/51) T. gondii seropositivity among sparrows in region of Pernambuco, Brazil. They also detected T. gondii DNA from four sparrows by Nested-PCR (Vilela et al 2011).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…No Brasil os estudos soroepidemiológicos da infecção por T. gondii em aves silvestres de vida livre também são escassos. As pesquisas foram realizadas na região Sudeste no Estado de São Paulo (Sogorb et al 1972, Sogorb et al 1977, Gonçalves et al 2013) e na região Nordeste no Estado da Bahia (Gondim et al 2010) e no Estado de Pernambuco, estudos foram realizados no continente (Vilela et al 2011) e no Arquipélago de Fernando de Noronha (Costa et al 2012). Em pombos-domésticos (Columba livia) sinantrópi-cos fo-ram realizados levantamentos sorológicos no Estado de São Paulo (Godoi et al 2010, De Lima et al 2011.…”
Section: Introductionunclassified